Independency of the Corruption Eradication Commission of the Republic of Indonesia (KPK RI) in Indicators of Independent Regulatory Agencies (IRAs) - Rizki Ramadani; Moch Andry W W Mamonto (Faculty of Law, Universitas Muslim Indonesia, Indonesia, 2018)
This research aims to know, analyze, and formulate the independency indicators of independent institutions based on the concept of Independent Regulatory Agencies (IRAs) in advanced countries (United States and Europe). Also as an efforts to examine and see the extent to which independent institutions in Indonesia meet these indicators. This study focuses on KPK institution that are well known as one of independent institutions in Indonesia. Although in practice it often rise the controversy and resistance from many parties. The method used in this legal research is normative legal research, conducted through literature study or secondary data. Data consists of legal materials primary, secondary and tertiary, which are then processed descriptive-prescriptively. The research also uses several approaches such as legal, conceptual, and case approach.